Explanation not Excuse: Attention Deficit Disorder, Collegiality and Coalition - Terry, David P. (Disability Studies Quarterly, 2016)
This ethnopoetic essay performs some of the professional, interpersonal and political challenges presented by ADHD and some of the ways in which non-visible disabilities intersect with other axes of privilege and accessibility.